Proyecto producción y comercialización de una bebida energizante natural a base de pitahaya - Miranda García, Katherine Lissette (2009)
Energy drinks are meant to increase endurance, avoid sleep, providing faster reactions between others. Its consumption has increased dramatically in recent years, and this is the reason why this project is based on the realization of a market study to determine the acceptance of the manufacture and marketing of natural energy drinks based on an exotic fruit called Pitaya. The first chapter includes introduction, objectives and historical overview of the fruit. In the second chapter the focusing is performed in the market study, the sampling mechanisms and the development of the hypothesis; evidence to allow us to determine significant findings of the needs in the population sample. The third chapter describes the technical study, which covers the location of the plant, suppliers, equipment and machinery that will be used for the elaboration and distribution of the product. In the fourth chapter describes the financial study, which shows whether the project is viable or not, also performing a long-term projection to determine the profitability of the project, and finally the conclusions about whether people are or are not be able to consume our product with the nutritional advantages it presents.